Review of lasers application in dentistry - Jokanović Vukoman; Trišić Dijana; Živković Marija (Serbian Medical Society - Dental Section, Belgrade, 2020)
In this paper the mechanism of stimulated emission is described as the fundamental of laser technology. The types of lasers from the aspect of their operation are also given. The particular attention is paid to dental lasers and their effect on healing processes in bone, dentin, enamel etc.